Enhancing the Treatability of Textile Wastewater in Biological Activated Sludge Process - Vo, Tam (VNU Journal of Science: Earth and Environmental Sciences, 2017)
In Vietnam, there are many technologies used  for the treating of textile wastewater. Microbiological step in most of cases is widely used because of its ecological and economical nature. However, this process has not generally taken effected due to the inhibition of microbes and other dyeing chemicals that are very durable, even toxic. In order to solve this problem, powdered activated carbon is added to enhance the exposure of the substrate with the activated sludge in treatment process. The results showed that the activated sludge system with powdered activated carbon is not inhibited, biomass is well developed compared to the activated sludge system without powdered activated carbon. The values of COD in treated wastewater by system with powdered activated carbon were approximately COD values specified in QCVN 13-MT:2015/BTNMT (B), while the values of COD in treated wastewater by system without powdered activated carbon were higher than that in QCVN 13-MT:2015/BTNMT (B) from 1.85 to 2.33 times.